Society Efforts in Preventing Dengue Fever in Bergaslor, Bergas, Semarang - Ratnawulan, Arie; Raffy Rustiana, Eunike; Made Sudana, I (Public Health Perspective Journal, 2019)
The number of Dengue Fever sufferers in Indonesia in 2017 was reported as many 59.047 cases with a total death of 444 people (incidence rate/morbidity rate=22,55 per 100,000 population and case fatality rate(CFR)/mortality rate =0,75%). This assumption is often overlooked, even though it is very influential on peoples efforts in making decisions,especially against prevention of dengue. The purpose of this study was to determine society efforts in addressing the prevention of Dengue Fever(DHF) in bergaslor, bergas,semarang. This research used descriptive research with a qualitative approach. The subjects in this study were 6 mothers in Bergaslor,Bergas,Semarang ,taken by snow ball sampling. The results of the study indicate that the prevention of Dengue Fever(DHF) by the society is the most important thing to do is to clean the house and the surrounding environment and use mosquito repellent. Some activities that are still lacking in prevention of Dengue Fever(DHF) are draining the bath,burying scraps, the irregular abate using and fogging.Jenis penelitian yang digunakan adalah jenis penelitian deskriptif dengan pendekatan kualitatif. Subyek dalam penelitian ini adalah 6 ibu di Desa Bergaslor Kecamatan Bergas Kabupaten Semarang diambil dengan cara snow ball sampling.Hasil penelitian menunjukkan upaya pencegahan penyakit demam berdarah yang dilakukan masyarakat yang paling utama dilakukan masyarakat adalah membersihkan rumah dan lingkungan sekitarnya dan pemakaian anti nyamuk. Kegiatan yang masih kurang dalam pencegahan DBD adalah menguras bak mandi, mengubur barang bekas, pemakaian abate dan foging yang kurang teratur.Adapun saran bagi masyarakat sangat diperlukan untuk ditanamkan sikap yang peduli terhadap penyakit DBD kepada anggota keluarga untuk memperkecil resiko terkena penyakit DBD.Keterlibatan kader kesehatan, kepala lingkungan, PKK, tokoh masyarakat, tokoh agama, dan lintas sektor lainnya perlu ditingkatkan agar dapat meningkatkan keberhasilan pelaksanaan P2M DBD.